A study of demographic and economic profile of COVID-19 mortalities in tertiary health care hospital setting - Kulshrestha, Alok; Gupta, Girjesh; Gumashta, Raghavendra; Mahor, Rajendra Singh; Kulshrestha, Manu (International Journal Of Community Medicine And Public Health, 2022)
Background: The health care system could not cope up with upsurge of cases being reported. This enormous magnitude of patient load derailed functionality of hospitals and has put in public health challenges to prevent subsequent pandemics and ensure all time readiness of health care system. This study focused to understand the interactive phenomenon among demographic and economic profile of COVID-19 mortalities in a hospital setting of a tertiary health care facility. Methods: A cross sectional study was undertaken using retrospective data analysis and qualitative study through group discussions among clinical subject specialist of various streams to assess and arrive at a reasoned cause analysis targeted towards prospective technical gains for institutional, individual and facility-based strengthening. Results: The age group 31-70 years had highest COVID-19 deaths (80%) with 51-70 years representing very high deaths (46.9%). Least mortalities were noted among those with occupation of agriculture (7.1%). Zone wise distribution shows that the joint family of east zone showed highest percentage of COVID-19 mortalities among females (22.2%) whereas it was lower among males (10.1%) however in the same zone and in the type of family. Conclusions: The study concludes of felt need for elaborate preparedness of programmatic, managerial and implementer-based facility support to enable health care facility for minimizing and preferably zeroing mortalities due to ongoing or future pandemics. It shall surely provide the quantum and directionality to the needed efforts by all stakeholders at various levels of interventions for sustainable gains directed towards universal health care.